Surgical Management of Adnexal Masses in Pregnancy - Nazia Sayed, Reema Fateh, Shah Abbas (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: The incidence of suspicious adnexal masses is on the rise during pregnancy due to advancement of ultrasonography in the modern era. The prevalence of adnexal masses varied from 6% to 25% in gestational age of <20 weeks during pregnancy. However, due to a paucity of large randomized studies, little is known regarding their treatment during pregnancy. The present study aimed to assess the surgical management of suspected adnexal masses during pregnancy. Material and Methods: This retrospective study was carried out on 28 suspected adnexal masses pregnant women in the Department of Gynecology, Saidu Group of Teaching Hospital Swat during the period from March 2022 to August 2022. Patients with definite indications were assessed through surgical intervention, tumor markers, MRI (Magnetic Resonance Imaging), and as per International Ovarian Tumour Analysis (IOTA) ultrasound rules. Pregnant women who had a laparoscopy or laparotomy before 20 weeks of pregnancy to treat an adnexal mass were enrolled. SPSS version 28 was used for data analysis. Results: The overall mean age was 28.4 ± 1.9 years with an age range from 18 years to 35 years. The mean gestational age was 16.4± 1.7 weeks. Of the total 28 suspected adnexal masses, the prevalence of benign and malignant cases were 22 (78.6%) and 6 (21.4%) respectively. Out of 28 cases, about 18 (64.3%) had laparoscopic surgery and 10 (35.7%) had laparotomy. The left upper quadrant entry technique was used in 17 (60.7%) cases. Due to extensive pelvic adhesion, 3 (10.7%) required conversion from laparoscopic to laparotomy surgery. The laparoscopic group lost considerably less blood (66.7 ±52.4 vs 148.9 ±178.0 mL, P.051) and had hospitalization for short duration (2.6 ±0.9 vs 3.7 ±1.2 days, P.005) than the laparotomy group. One woman miscarried shortly after undergoing surgery. Obstetric outcomes did not differ significantly between the laparoscopy and laparotomy groups. Conclusion: The present study concluded that surgical treatment of adnexal masses appears to benefit both the mother and the fetus during pregnancy. Thorough clinical examination, individualized imaging, and prompt action assist in the identification and management of suspected adnexal masses during pregnancy. Keywords: Surgical management, Adnexal masses, Pregnancy, Laparoscopy, Laparotomy